High‐Performance Organic Heterojunction Phototransistors Based on Highly Ordered Copper Phthalocyanine/para‐Sexiphenyl Thin Films. (27th December 2016) - Qian, Chuan; Sun, Jia; Kong, Ling‐An; Gou, Guangyang; Zhu, Menglong; Yuan, Yongbo; Huang, Han; Gao, Yongli; Yang, Junliang
Abstract : High‐performance organic heterojunction phototransistors are fabricated using highly ordered copper phthalocyanine (CuPc) and para ‐sexiphenyl ( p ‐6P) thin films. The p ‐6P thin film plays an important role on the performance of CuPc/ p ‐6P heterojunction phototransistors. It acts as a molecular template layer to induce the growth of highly ordered CuPc thin film, which dramatically improves the charge transport and decreases the grain boundaries. On the other hand, the p ‐6P thin film can form an effective heterojunction with CuPc thin film, which is greatly helpful to enhance the light absorption and photogenerated carriers. Under 365 nm ultraviolet light irradiation, the ratio of photocurrent and dark current and photoresponsivity of CuPc/ p ‐6P heterojunction phototransistors reaches to about 2.2 × 10 4 and 4.3 × 10 2 A W −1, respectively, which are much larger than that of CuPc phototransistors of about 2.7 × 10 2 and 7.3 A W −1, respectively. A detailed study carried out with current sensing atomic force microscopy proves that the photocurrent is predominately produced inside the highly ordered CuPc/ p ‐6P heterojunction grains, while the photocurrent produced at the boundaries between grains can be neglected. The research provides a good method for fabricating high‐performance organic phototransistors using a combination of molecular template growth and organic heterojunction. Abstract : High‐performance organic heterojunction phototransistors are fabricated using highly ordered copper phthalocyanine (CuPc) and para ‐sexiphenyl ( p ‐6P) thin films. The ratio of photocurrent and dark current and photoresponsivity reach to about 2.2 × 10 4 and 4.3 × 10 2 A W −1, respectively. A detailed study is carried out with current sensing atomic force microscopy.